PENGELOLAAN EKOWISATA DAN PENTINGNYA PENERAPAN CHSE - Liliana Dewi; Gagih Pradini; Muhammad Andriansyah Satritama; Reza Ardian Putra (Bajang Institute, 2023)
Godong Ijo is an educational tourist attraction that carries the concept of